Chemical composition of monsoon rainwater over Bhopal) Madhya Pradesh (India) during 1977 and 1978 (MAUSAM, 1981)
A preliminary and systematic study of the chemical composition of monsoon rainwater over Bhopal has been carried out during the years 1977 and 1978. The analytical results reveal that the total minerals of the rainwater is governed by the meteorological and geographical parameters. A definite pattern, however, could not be ascertained and the concentration of different ions vary considerably. Bicarbonate is the predominant anion and calcium is the predominant cation. Most of the ions originate from the non-marine sources, although marine origin is also likely to contribute for the presence of some ions in the rainwater. The presence of trace elements such as strontium, copper, zinc, manganese and iron have been recorded but lithium and nickel could not be detected in the local rainwater samples during the period.